CDK4 Amplification in Esophageal Squamous Cell Carcinoma Associated With Better Patient Outcome - Huang, Jie; Wang, Xiang; Zhang, Xue; Chen, Weijie; Luan, Lijuan; Song, Qi; Wang, Hao; Liu, Jia; Xu, Lei; Xu, Yifan; Shen, Licheng; Tan, Lijie; et al. (Frontiers in Genetics, 2021)
In the present study, we aimed to investigate the clinical and prognostic values of CDK4 amplification and improve the risk stratification in patients with esophageal squamous cell carcinoma. CDK4 amplification was analyzed by fluorescence in situ hybridization using tissue microarray consisting of representative tissues of 520 patients with esophageal squamous cell carcinoma, and its correlation with clinicopathological features and clinical outcomes were evaluated. CDK4 amplification was found in 8.5% (44/520) of patients with esophageal squamous cell carcinoma. CDK4 amplification was negatively correlated with disease progression (P=0.003) and death (P=0.006). Patients with CDK4 amplification showed a significantly better disease-free survival (P=0.016) and overall survival (P=0.023) compared with those patients without CDK4 amplification. When patients were further stratified into I-II stage group and III-IV stage group, CDK4 amplification was significantly associated with both better disease-free survival (P=0.023) and overall survival (P=0.025) in I-II stage group rather than III-IV stage group. On univariate and multivariate analysis, invasive depth and CDK4 amplification were associated with disease-free survival and overall survival. Taken together, CDK4 amplification was identified as an independent prognostic factor for survival which could be incorporated into the tumor-node-metastasis staging system to refine risk stratification of patients with esophageal squamous cell carcinoma.